Bringing eCare platforms to the market. (3rd July 2017) - Vannieuwenborg, Frederic; Van der Auwermeulen, Thomas; Van Ooteghem, Jan; Jacobs, An; Verbugge, Sofie; Colle, Didier
ABSTRACT: Due to changes in the demographic situation of most Western European countries, interest in Information and Communication Technologies (ICT)-supported care services is growing fast. eCare services that foster better care information exchange, social involvement, lifestyle monitoring services, etc., offered via ICT platforms, integrated in the homes of the elderly are believed to be cost-effective. Additionally, they could lead to an increased quality of life of both care receiver and (in)formal caregiver. Currently, adoption and integration of these eCare platforms (eCPs) is slowed down by several barriers such as unclear added value, a lack of regulations, or lack of sustainable financial models. In this work, the added value of eCPs is identified for the several involved key actors such as the care receiver, the (in)formal care providers, and the home care organizations. In a second step, several go-to-market strategies are formulated. Because the gap between the current way of providing home care and providing home care supported by a fully integrated eCP seems too big to bridge in one effort, a migration path is provided for stepwise integration and adoption of eCPs in the current way of home care provisioning.